2008
DOI: 10.1038/leu.2008.261
|View full text |Cite
|
Sign up to set email alerts
|

The addition of rituximab to front-line therapy with CHOP (R-CHOP) results in a higher response rate and longer time to treatment failure in patients with lymphoplasmacytic lymphoma: results of a randomized trial of the German Low-Grade Lymphoma Study Group (GLSG)

Abstract: Lymphoplasmacytic lymphoma (LPL) is an indolent lymphoma with moderate sensitivity to conventional chemotherapy. This study investigated whether the addition of rituximab to standard chemotherapy improves treatment outcome in LPL and the subgroup of LPL patients fulfilling the criteria of Waldenstroem's macroglobulinemia (WM). A total of 69 patients with previously untreated LPL were enrolled into the trial; 64 patients were evaluable for treatment outcome. In all, 48 of the 64 LPL patients fulfilled the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(88 citation statements)
references
References 30 publications
3
80
1
4
Order By: Relevance
“…Bendamustine with rituximab have also shown a PFS of 69 months, but the numbers were small. 18 Ibrutinib was recently approved for treatment-naïve and relapsed/refractory WM patients; however, available data are based only on previously treated patients and long-term follow up is still missing. Furthermore, ibrutinib requires continuous treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Bendamustine with rituximab have also shown a PFS of 69 months, but the numbers were small. 18 Ibrutinib was recently approved for treatment-naïve and relapsed/refractory WM patients; however, available data are based only on previously treated patients and long-term follow up is still missing. Furthermore, ibrutinib requires continuous treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical input data (efficacy and safety), treatment dosing schedules, overall population mortality were used to populate the model and derived respectively from global trials (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) as well as published literature [1,16,[18][19][20][21][22][23][24]. Comparative efficacy for ibrutinib vs. CTP was derived from a multivariate Cox proportional hazard model performed to estimate the hazard ratio (HR) of the PFS for ibrutinib vs. CTP [1,16,[18][19][20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study is to estimate, from the Italian National Health System (NHS) perspective, the incremental cost-effectiveness ratio (ICER) of ibrutinib in relapsing/ refractory (R/R) WM, compared with the current therapeutic pathways (CTP) applied to WM: fludarabine + cyclophosphamide + rituximab (FCR), bortezomib + rituximab (BOR), rituximab + cyclophosphamide + doxorubicin + vincristine + prednisone (RCHOP), bortezomib + dexamethasone + rituximab (BDR), dexamethasone + rituximab + cyclophosphamide (DRC), and bendamustine/rituximab (BR) [1,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The one recently published, large randomized trial in WM does provide some guidance in the choice of therapies for WM [22]. This trial showed major clinical benefit in response rate, PFS, and OS from the addition of rituximab to conventional chemotherapy (CHOP; cyclophosphamide, doxorubicin, vincristine, prednisone).…”
mentioning
confidence: 99%